Evaluation of Factors Contributing to the Effectiveness of Internal Audit Quality in Pakistani Commercial Banks - Madiha Afzal (International Journal of Financial Studies, 2023)
The Pakistani banking sectors facing numerous challenges because of poor internal audit quality. Internal audit quality has long been a source of contention. The current study examines the factors that affect internal audit quality in Pakistani commercial banks. Internal audit quality evaluated through potential factors such as competence, objectivity, performance, board audit committee support, and independence. Along with these factors, a questionnaire designed to determine the nature of the problems confronting Pakistani commercial banks. 102 questionnaires disseminated among the chief internal auditor, chief financial officer, board audit committee, and managers of 26 listed commercial banks. The impact of the factors on internal audit quality investigated using a binary logit regression model and multiple correspondence analyses. Findings show that performance, competence, and objectivity factors are statistically positively significant that influenced internal audit quality to improve it. This research helps improve the internal audit quality in Pakistani commercial banks.